Prospek Penerapan Blockchain dalam Pengelolaan Zakat sebagai Upaya Mewujudkan Sustainable Development Goals (SDGs): Sebuah Harapan dan Tantangan - Nur Sulistiyaningsih; Alisha Vinia Alethea Majid; Putri Melati Nur Hidayah; Laksito Adhi Priwegga; Muhammad Daffa Manggala Budhi Kusumo (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This article discusses the prospects for implementing blockchain in zakat as an effort to realize Sustainable Development Goals. Blockchain technology has great potential to change the way zakat collection, management and distribution is carried out. Zakat fund management often faces complex challenges, including lack of transparency, low accountability, and uncertainty in the distribution of funds. This can result in misuse of funds, inability to achieve set targets, and low public trust in institutions that manage zakat. The application of blockchain can help zakat institutions increase accountability and effectiveness in distributing zakat to the right targets. This article uses a qualitative descriptive research approach to explore the prospects for applying blockchain technology in zakat management as part of efforts to achieve Sustainable Development Goals (SDGs). In the research results, we found that the application of blockchain technology in zakat management can increase transparency, accountability, efficiency, improve the economy in the aspects of poverty, hunger, health services and education. In conclusion, the application of blockchain in zakat has bright prospects for increasing efficiency and transparency, as well as supporting efforts to realize Sustainable Development Goals (SDGs).